2012
DOI: 10.1111/j.1471-0528.2012.03283.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in Dutch maternal mortality

Abstract: Objective To study regional differences in maternal mortality in the Netherlands.Design Confidential inquiry into the causes of maternal mortality.Setting Nationwide.Population A total of 3 108 235 live births and 337 maternal deaths.Methods Data analysis of all maternal deaths in the period 1993-2008.Main outcome measure Maternal mortality.Results The overall national maternal mortality ratio was 10.8 per 100 000 live births. In the 12 provinces of the Netherlands, the maternal mortality ratio ranged from 6.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The distribution of NSS in our study population (IQR −1.13–0.77) approximately resembles the distribution of NSS across the Netherlands (IQR −0.57–0.71). The lower limit of the IQR of NSS in our study population indicates the presence of deprived neighbourhoods, which is to be expected in the urban city of Rotterdam [31]. Women from 193 different neighbourhoods were included in the study, which indicates a large neighbourhood heterogeneity within our study population.…”
Section: Discussionmentioning
confidence: 86%
“…The distribution of NSS in our study population (IQR −1.13–0.77) approximately resembles the distribution of NSS across the Netherlands (IQR −0.57–0.71). The lower limit of the IQR of NSS in our study population indicates the presence of deprived neighbourhoods, which is to be expected in the urban city of Rotterdam [31]. Women from 193 different neighbourhoods were included in the study, which indicates a large neighbourhood heterogeneity within our study population.…”
Section: Discussionmentioning
confidence: 86%
“…The incidence of severe PPH was analyzed per province and in the four largest cities because previous studies reported that perinatal outcomes in these cities are inferior to those in the other regions (provinces) of the Netherlands [ 19 - 21 ]. For the two largest cities, Amsterdam and Rotterdam, the incidence of severe PPH was analyzed across neighborhoods.…”
Section: Methodsmentioning
confidence: 99%
“…Between country variation of maternal mortality was the key focus of our study, but we acknowledge that national rates may mask within country variations, as previously highlighted in France and in the Netherlands. 29 30 Although the characteristics of women may vary from one region to another, a meaningful national profile of pregnant women exists, and the organisation of care and recommendations for good practice are defined according to a national standard. Furthermore, the appropriate regional categorisation may vary from one country to another; thus, in the two studies cited above, France isolated the overseas territories and the Netherlands the urban regions, in relation to each national question of healthcare organisation.…”
Section: Discussionmentioning
confidence: 99%